UNKNOWN TO THE EXISTENCE OF SELLERS AS A BASIS FOR FULFILLMENT OF CERTAIN CIRCUMSTANCES IN THE REGISTRATION OF THE PROCESS OF RETURNING THE NAME OF THE TRANSFER OF PROPERTY RIGHTS TO LAND FROM BUILDING USE RIGHTS: (CASE STUDY BANYUMAS DISTRICT COURT DECISION NUMBER 20/PDT.G/2020/PN.BMS) - Desira Sari Agrianti; Fx Arsin Lukman (Awang Long Law Review, 2022)
This study aims to examine the existence of the seller as well as the right holder in the SHGB in the process of registering the name of the SHGB from the name of the seller/defendant to the name of the plaintiff. The judge's consideration in this decision considered that due to the sale and purchase of SHGB Number 00245, the name could not be changed to the name of the Plaintiff solely because Defendant's place of residence was unknown. This consideration became the basis for the judge in based on the principle of justice and the principle of legal certainty to grant the petite of the four Plaintiffs' claims in the form of a decision stating that the Plaintiff had the right to reverse the name of SHGB No. 00245 which is located in Kelurahan Kelurahan/Wiradadi Village, Sokaraja Subdistrict, Banyumas Regency at the Office of the Ministry of Agrarian and Spatial Planning/National Land Agency (ATR/BPN) Banyumas Regency (Co-Defendant) from on behalf of PT Tito Rumpun Sehati (Defendant I) to Titi Kuntarsih (Plaintiff). Based on the explanation of the background above, this research intends to formulate a problem formulation to examine the following two research questions : (1) How is the implementation of the fulfillment of certain conditions in the process of transferring the name of the transfer title to a parcel of land with a right of ownership of a building without a PPAT deed? and (2) What are the implications of the judge's consideration regarding not knowing the whereabouts of the seller as the basis for fulfilling certain conditions in the process of transferring the title to a parcel of land with property rights from the right to use a building without a PPAT deed in the Banyumas District Court Decision Number 20/Pdt.G/2020 /PN.Bms.